Price formation in monopolistic markets with endogenous diffusion of trading information: An experimental approach - Morten Søberg (Statistics Norway, Research Department, 2002)
This paper reports on price formation in experimental markets in which a single seller trades with four buyers. Transactions occur if either a buyer accepts an offer to sell from the seller, or the seller accepts an offer to buy from a buyer. The dissemination of such offers is endogenous in that the seller determines which buyer(s) should be informed about offers to sell, whereas each buyer may broadcast his offer to buy to any of the residual buyers. Complete dissemination of offers is consistent with conventional double-auction trading rules. The result is two-fold. First, the diffusion of trading information is incomplete, in that neither the single seller nor the buyers inform all market participants about offers. Second, observed prices and the number of transactions are in line with the competitive theoretic benchmark.
Keywords: C90; D42; G14; 330; Experimental economics; market structure; trading information